2004
DOI: 10.1080/14992020400050075
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and attitudes among Swedish workers regarding the risk of hearing loss

Abstract: The beliefs and attitudes regarding the risk of hearing loss and their impact on hearing protector use were investigated among Swedish workers. A questionnaire, developed by the US National Institute for Occupational Safety and Health (NIOSH), was used. The study objective was to assess workers' attitudes towards using hearing protection devices (HPDs) and to enhance the ability of workers to protect themselves from occupational hearing loss. Ninety-five per cent of the respondents were aware that loud noise c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 8 publications
5
40
0
4
Order By: Relevance
“…Regarding schooling, 50% of the individuals in the Study Group (SG) and 41.67% of those in the Control Group (CG) have a High School diploma (Table 1). A similar result was reported in another study conducted in Brazil with laundry workers, in which the authors observed that most of the participants presented High School level (24) . In the evaluation of the Educational Intervention conducted with hospital laundry workers, when comparing the questionnaires between the groups (Table 2), it was possible to observe that, in Questionnaire A -prior to the workshops, only one question (no.13) presented difference between the groups, showing that all workers had similar knowledge, attitudes, and practices.…”
Section: Discussionsupporting
confidence: 74%
“…Regarding schooling, 50% of the individuals in the Study Group (SG) and 41.67% of those in the Control Group (CG) have a High School diploma (Table 1). A similar result was reported in another study conducted in Brazil with laundry workers, in which the authors observed that most of the participants presented High School level (24) . In the evaluation of the Educational Intervention conducted with hospital laundry workers, when comparing the questionnaires between the groups (Table 2), it was possible to observe that, in Questionnaire A -prior to the workshops, only one question (no.13) presented difference between the groups, showing that all workers had similar knowledge, attitudes, and practices.…”
Section: Discussionsupporting
confidence: 74%
“…The audiometry exams were classified following the Regulatory Norm n. 7 in its Annex I, in The Ministry of Labor. 2) Application of the pre-intervention questionnaire (A) on workers: it was used a validated questionnaire, semi-structure, with closed questions entitled "Beliefs and Attitudes about Hearing Protection", originated from NIOSH (1996) 16,17 in the United States and translated to Portuguese in 2008 5 . 3) Conduction of three workshops as part of the educational actions of HPP: the strategy of the workshops was based on some aspects of the Participative Methodology.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies 29-93% of workers were aware about the health effects of noise [4,[12][13][14]. Svensson et al stated that 95% of the Swedish workers were aware that loud noise could damage their hearing [15]. In addition, one study in Malaysia found that 36 % of the noise exposed workers knew that exposure to excessive noise results in hearing loss [16].…”
Section: Discussionmentioning
confidence: 99%